NIGERIA AND THE PALESTINIAN - ISRAELI CONFLICT 1960 - 2006 (2012)
The consequences of the United Nations partitioning of Palestine in 1948 have been recurrent wars and peace processes in the Middle East, as the conflict has remained intractable. While studies have been conducted on these wars and peace processes, there has been no systematic study on Nigeria's policy and role in the Middle East crisis and peace process. This study, therefore, focused on Nigeria's foreign policy and role in the Palestinian-Israeli conflict. It examined the origin and consequences of the Palestinian conflict and identified the determinants of Nigeria's Policy in the Middle East. The data for the study were gathered through documentary research, questionnaire administration, observation and interview. A total of 234 questionnaires were administered to Nigerian students, lecturers, and senior civil servants. Delphi panel interview was conducted among Nigerian and non- Nigerian ambassadors posted to the Middle East. Furthermore, secondary data were obtained from books, journals, newspapers, and the Internet. Descriptive statistics was used to analyze aspects of the data that were quantitative. The unilateral partitioning of Palestine into Jewish and Palestinian States and the subsequent creation of the Jewish State in 1948 was the major cause of the conflict between Israel and the Arab States. A majority of respondents (61.1%) preferred to describe Nigeria's foreign policy on the Palestinian-Israeli conflict and peace process as that of neutrality. The policy of neutrality was determined by Nigeria's ethnic and religious diversity according to 62.4% of the respondents. In weighing the factors that determined Nigeria's policy in the Palestinian-Israeli conflict and peace process, 47% of the respondents chose Nigeria's membership of regional and International Organization especially the United Nations and the Organization of Petroleum Exporting Countries, 35.5% chose economic factors (oil), 26.9% selected the ruling elite, 12% marked geographical factors, 10.7% chose military factors, 9.4% marked public opinion, 8.1% chose pressure group action, while 7.7% chose political parties. Despite Nigeria's huge resources and leadership role in Africa, it has not been a major player in the Middle East Crisis. The key actors in the conflict and peace process have been the United States of America, the former Soviet Union (now Russia), Israel, Syria, Egypt, Lebanon, Palestine Liberation Organization and the United Nations. Nigeria pursued a pragmatic foreign policy which was determined essentially by two main factors: Nigeria's multi ethnic and religious composition, and its membership of regional and international organizations. There is a national consensus about what role Nigeria should play in the global arena. Nigeria is commonly portrayed as secular, Afrocentric and pan-Africanist. However, with the Middle East, this projection and consensus appeared blurred. Because Nigeria does not have a strategic interest in Israel, its foreign policy and role in the conflict and peace process were anchored on the interest of other nations and organizations and not on its national interest. Nigeria's foreign policy should be premised on its national interests in relation to the Palestinian-Israeli conflict. These interests need to be explicitly articulated and pursued, for in the final analysis